THE INFLUENCE OF FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDES TOWARDS SOCIETY INVESTMENT DECISION IN MAKASSAR - Abbas, Ismawati; Widasari, Firda (Jurnal Iqtisaduna, 2019)
Every individual needs treasure to fulffill every of his/her life needs so individual will always trying to get the property, one of the way by doing the investment decision. This Research purposed to test the Influence of Financial Knowledge and Financial Attitude towards society investment decision at Makassar City with risk tolerance as control variable. Sampling technique using probability sampling method with amount of sample minimum of 60. From the tests performed based on the result of partial test (test t) for financial knowledge and financial attitude show significant positive impact towards investment decision. It means that the higher the knowledge and the better financial attitude of a person, the better investment decision will be made. Contol variable analysis with using partial correlation test shows that risk tolerance could controlled the relation of financial knowledge and financial attitude towards investment decision.